Degenerative xanthate transfer to olefins under visible-light photocatalysis - Kaga, Atsushi; Wu, Xiangyang; Lim, Joel Yi Jie; Hayashi, Hirohito; Lu, Yunpeng; Yeow, Edwin K. L.; Chiba, Shunsuke (Beilstein Journal of Organic Chemistry, 2018)
The degenerative transfer of xanthates to olefins is enabled by the iridium-based photocatalyst [Ir{dF(CF3)ppy}2(dtbbpy)](PF6) under blue LED light irradiation. Detailed mechanistic investigations through kinetics and photophysical studies revealed that the process operates under a radical chain mechanism, which is initiated through triplet-sensitization of xanthates by the long-lived triplet state of the iridium-based photocatalyst.
Keywords: energy transfer; olefin; photocatalysis; radical; xanthate